Identifikasi Kesesuaian Lokasi Penempatan Rumah Ikan di perairan Pulau Kalih Kabupaten Serang - Aulia Hikmah Nanto; Adi Susanto; Muta Ali Khalifa (Jurnal Perikanan dan Kelautan, 2023)
Fish apartment is a hollow building composed of solid objects placed in waters which is intended to replace the ecological function of natural habitat for fish resources. Therefore, the placement of fish houses must be done taking into account certain criteria. The aim of this research is to determine the suitability of the location for placing fish apartment in the waters of Kalih Island, Serang Regency, Banten Province. Survey and data collection activities were carried out in November 2023. The data collected included oceanographic characteristics, water quality and existing utilization activities carried out by the community in the waters of Kalih Island. Location suitability analysis is carried out using a scoring method with certain criteria. The results show the waters of Kalih Island are not suitable for placing fish apartment with the final scores obtained being 210 and 220. Parameters that are less suitable include water brightness, substrate type, safety factors and low community participation.